The social effects of native title : recognition, translation, coexistence - Smith, Benjamin R.; Morphy, F. (Frances), 1949- (Research monograph (Australian National University. Centre for Aboriginal Economic Policy Research) ;, 2007)
"The papers in this collection reflect on the various social effects of native title. In particular, the authors consider the ways in which the implementation of the Native Title Act 1993 (Cwlth), and the native title process for which this Act legislates, allow for the recognition and translation of Aboriginal law and custom, and facilitate particular kinds of coexistence between Aboriginal title holders and other Australians. In so doing, the authors seek to extend the debate on native title beyond questions of practice and towards an improved understanding of the effects of native title on the social lives of Indigenous Australians and on Australian society more generally"--Publisher's description